A method for processing a quantum dot light-emitting layer, an electroluminescent device and a method for preparing the same

By spin-coating proton solvent on the quantum dot luminescent layer and heat treatment, the problem of electron and hole injection imbalance is solved, the exciton formation probability and luminous efficiency are improved, and the performance of electroluminescent devices is significantly improved.

CN114649490BActive Publication Date: 2025-02-25HEFEI FUNA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210238401.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-11
Publication Date
2025-02-25
Estimated Expiration
2042-03-11

AI Technical Summary

Technical Problem

In the existing quantum dot light emitting diodes, the infusion of electrons and holes leads to a decrease in the probability of exciton formation, affecting device performance, and the large accumulation of electrons makes the quantum dot in a state of charge, reducing the luminous efficiency.

Method used

By spin-coating the protic solvent at a rotation speed of 8000-10000rpm/min on the quantum dot luminescent layer, the time is 0.5-1.5 min, and heat treatment is performed to clean the organic ligands that have not been cleaned off on the surface, promoting the rearrangement and reorganization of the quantum dots. , improve the recombination efficiency of electrons and holes.

Benefits of technology

Enhanced the effective recombination and exciton lifetime of electron-holes, and improve the performance of electroluminescent devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114649490B_ABST
    Figure CN114649490B_ABST
Patent Text Reader

Abstract

The present application embodiment provides a method for processing a quantum dot light-emitting layer, an electroluminescent device and a method for preparing the same, and relates to the field of electronic light-emitting devices. The present application embodiment provides a method for processing a quantum dot light-emitting layer, comprising the following steps: spin coating a proton solvent on the quantum dot light-emitting layer at a speed of 8000-10000 rpm / min for 0.5-1.5 min, and then performing a heat treatment until the proton solvent evaporates. The method for processing the quantum dot light-emitting layer of the present application embodiment can enhance the effective recombination of electrons and holes and the exciton lifetime, thereby improving the performance of the electroluminescent device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic light-emitting devices, and in particular to a method for processing a quantum dot light-emitting layer, an electroluminescent device and a method for preparing the same. Background Art

[0002] Quantum dot light emitting diodes (QLEDs) have the advantages of high color purity, adjustable luminous color, and good stability, making them a favorable competitor for the next generation of display technology; however, the main reason that has always restricted their industrialization is the efficiency and life span of the device.

[0003] This is mainly because in common quantum dot light-emitting diodes, ZnO is used as an electron transport layer, and the electron mobility reaches 2*10-3*10cm 2 v / s, so that electrons can be easily injected into the quantum dot light-emitting layer through ZnO, while the organic matter as the hole transport layer has a lower mobility than the inorganic material because its molecules interact through van der Waals forces, resulting in an imbalance in the injection of electrons and holes, reducing the probability of forming excitons in the quantum dot light-emitting layer, thereby affecting the device performance; at the same time, the imbalance between electrons and holes will lead to a large accumulation of electrons in the quantum dot light-emitting layer, making the quantum dots in a charged state, which will cause the Auger recombination process. The Auger recombination will reduce the luminescence efficiency of the quantum dots, thereby affecting the performance of the device. Summary of the invention

[0004] The purpose of the embodiments of the present application is to provide a method for processing a quantum dot light-emitting layer, an electroluminescent device and a method for preparing the same, which can enhance the effective recombination of electrons and holes and the exciton lifetime, thereby improving the performance of the electroluminescent device.

[0005] In a first aspect, an embodiment of the present application provides a method for processing a quantum dot light-emitting layer, comprising the following steps:

[0006] The proton solvent is spin-coated on the quantum dot light-emitting layer at a rotation speed of 8000-10000 rpm / min for 0.5-1.5 min, and then heat-treated to volatilize the proton solvent.

[0007] In the above implementation process, the organic ligands are brought in the quantum dot synthesis process. Although some of the organic ligands will be washed away in the subsequent quantum dot cleaning process, some organic ligands will still exist. On this basis, the proton solvent spin-coated on the quantum dot light-emitting layer at high speed can better clean the long-chain organic ligands that have not been washed away on the surface of the quantum dot, reducing the defects caused by the presence of organic ligands on the surface of the quantum dot light-emitting layer; at the same time, during the cleaning process, the quantum dot crystals can be relatively moved and rearranged as the proton reagent is flushed, and the quantum dots are reorganized in order to reduce the surface energy of the unpassivated surface of the quantum dots after the organic ligands are removed. Furthermore, the quantum dot film crystals treated with proton solvents will show uniform diffraction rings and have uniform crystal orientation. The uniform crystal orientation can promote the effective recombination of electrons and holes in the quantum dot film, enhance the exciton lifetime, and thus effectively improve the device performance.

[0008] In a possible implementation, the protic solvent includes at least one of a combination consisting of methanol, ethanol, tert-butanol, and benzyl alcohol.

[0009] In the above implementation process, high-speed spin coating of proton solvent alcohols on the quantum dot light-emitting layer can effectively enhance the electron-hole recombination and exciton lifetime, thereby improving the performance of the electroluminescent device.

[0010] In a possible implementation, the amount of the proton solvent spin-coated on the quantum dot light-emitting layer per unit centimeter area is 0.5-2 ml.

[0011] In the above implementation process, controlling the spin coating amount of the proton solvent on the quantum dot light-emitting layer is beneficial to enhancing the electron-hole recombination and exciton lifetime, thereby improving the performance of the electroluminescent device.

[0012] In a possible implementation, the material of the quantum dot light-emitting layer is a quantum dot with an organic ligand connected to the surface;

[0013] The quantum dots are selected from at least one of the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, PbS, PbSe, PbTe, GaP, GaAs, InP, InAs and binary, ternary, and quaternary II-VI compounds;

[0014] And / or, the quantum dot is a perovskite semiconductor; the general structural formula of the perovskite semiconductor is AMX3 or BMX3, wherein A is Cs, and B is selected from CH3(CH2)n-2NH3 + or NH3(CH2)nNH3 2+, and n≥2, M is selected from at least one of the group consisting of Pb, Sn, Cu, Ni, Cd, Cr, Mn, Co, Fe, Ge, Yb and Eu, and X is selected from at least one of the group consisting of Cl, Br and I.

[0015] In the above implementation process, organic ligands can modify the defects on the surface of quantum dots to prevent the quantum dots from agglomerating with each other and causing fluorescence quenching. Perovskite semiconductors as quantum dots have the advantages of narrow luminescence, wide color gamut, high quantum efficiency, high carrier mobility, and low-cost preparation.

[0016] In one possible implementation, an electroluminescent device includes: an ITO substrate, a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer and a metal cathode, which are stacked in sequence from bottom to top, wherein the surface of the quantum dot light-emitting layer close to the electron transport layer is processed using the processing method of the quantum dot light-emitting layer.

[0017] In the above implementation process, the ITO substrate, hole injection layer, hole transport layer, quantum dot light-emitting layer, electron transport layer and metal cathode are stacked in sequence from bottom to top to form a complete electroluminescent device.

[0018] In a possible implementation, the material of the hole injection layer is selected from the group consisting of PEDOT:PSS, PTPDES, PTPDES:TPBAH, PFO-co-NEPBN, PFO-co-NEPBN:F4-TCNQ, MoO x , WO x , NiO and CuO.

[0019] In the above implementation process, the hole injection layer can reduce the potential barrier for injecting holes from the anode, so that holes can be effectively injected from the anode into the device while ensuring the injection of carriers.

[0020] In a possible implementation, the material of the hole transport layer is selected from at least one of the group consisting of TFB, PVK, TCTA, TPD, Poly:TPD and CBP.

[0021] In the above implementation process, the hole transport layer enables the recombination of holes and electrons injected from the electrode to occur in the quantum dot light-emitting layer.

[0022] In a possible implementation, the material of the electron transport layer is selected from at least one of the group consisting of ZnO, TiO2, SnO2 and Alq3.

[0023] In the above implementation process, the electron transport layer enables the recombination of electrons and holes injected from the metal cathode to occur in the quantum dot light-emitting layer.

[0024] In a second aspect, the present invention provides a method for preparing an electroluminescent device, comprising the following steps:

[0025] A hole injection layer and a hole transport layer are sequentially formed on an ITO substrate;

[0026] A quantum dot light-emitting layer is formed on the hole transport layer, and a proton solvent is spin-coated on the quantum dot light-emitting layer at a speed of 8000-10000 rpm / min for 0.5-1.5 min, and then a heat treatment is performed to volatilize the proton solvent at a temperature of 80-150° C. for 10-30 min;

[0027] An electron transport layer and a metal cathode are sequentially formed on the processed quantum dot light-emitting layer.

[0028] In the above implementation process, the electroluminescent device is prepared according to the above preparation method, which can effectively improve the performance of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 A film formation diagram of a quantum dot light-emitting layer in an electroluminescent device provided in Example 1 of the present application;

[0031] Figure 2 A film formation diagram of a quantum dot light-emitting layer in an electroluminescent device provided in Comparative Example 1 of the present application;

[0032] Figure 3 A film formation diagram of a quantum dot light-emitting layer in an electroluminescent device provided in Example 2 of the present application;

[0033] Figure 4 This is a film formation diagram of a quantum dot light-emitting layer in an electroluminescent device provided in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0035] The following is a detailed description of a method for processing a quantum dot light-emitting layer, an electroluminescent device and a method for preparing the same in an embodiment of the present application.

[0036] The present invention provides a method for preparing an electroluminescent device, comprising the following steps:

[0037] (1) A hole injection layer and a hole transport layer are sequentially formed on an ITO substrate.

[0038] In some embodiments, the material of the hole injection layer is selected from the group consisting of PEDOT:PSS, PTPDES, PTPDES:TPBAH, PFO-co-NEPBN, PFO-co-NEPBN:F4-TCNQ, MoO x , WO x , NiO and CuO. Optionally, the material of the hole injection layer is PEDOT:PSS, PTPDES, PTPDES:TPBAH, PFO-co-NEPBN, PFO-co-NEPBN:F4-TCNQ, MoO x , WO x , NiO, CuO, a mixture of PEDOT:PSS and PTPDES, a mixture of PEDOT:PSS and PTPDES:TPBAH, a mixture of PEDOT:PSS and PFO-co-NEPBN, or a mixture of PEDOT:PSS and PFO-co-NEPBN:F4-TCNQ.

[0039] In some embodiments, the material of the hole transport layer is selected from at least one of the group consisting of TFB, PVK, TCTA, TPD, Poly:TPD and CBP. Optionally, the material of the hole transport layer is TFB, PVK, TCTA, TPD, Poly:TPD, CBP, a mixture of TFB and PVK, a mixture of TFB and TCTA, a mixture of TFB and TPD, a mixture of TFB and Poly:TPD, a mixture of TFB and CBP, a mixture of PVK and TCTA, a mixture of PVK and TPD, a mixture of PVK and Poly:TPD, or a mixture of PVK and CBP.

[0040] (2) forming a quantum dot light-emitting layer on the hole transport layer, and then treating the quantum dot light-emitting layer, the treatment method comprising the following steps: spin coating the quantum dot light-emitting layer with a proton solvent at a rotation speed of 8000-10000 rpm / min for 0.5-1.5 min, the spin coating method is usually to drip the proton solvent while spin coating to improve the uniformity of the proton solvent coverage; then heat treating until the proton solvent is volatilized, the heat treatment temperature is 80-150°C, and the heat treatment time is 10-30 min.

[0041] In some embodiments, the protic solvent includes at least one of a composition consisting of methanol, ethanol, tert-butanol, and benzyl alcohol. Optionally, the protic solvent is one of methanol, ethanol, tert-butanol, benzyl alcohol, a mixture of methanol and ethanol, a mixture of methanol and tert-butanol, a mixture of methanol and benzyl alcohol, a mixture of ethanol and tert-butanol, a mixture of ethanol and benzyl alcohol, or a mixture of tert-butanol and benzyl alcohol, or a solution of the above selected with water.

[0042] In some embodiments, the amount of proton solvent spin-coated on the quantum dot light-emitting layer per centimeter area is 0.5-2 ml. Optionally, the amount of proton solvent spin-coated on the quantum dot light-emitting layer per centimeter area is 0.5-1.5 ml, and for example, the amount of proton solvent spin-coated on the quantum dot light-emitting layer per centimeter area is 0.5 ml, 0.6 ml, 0.7 ml, 0.8 ml, 0.9 ml, 1 ml, 1.1 ml, 1.2 ml, 1.3 ml, 1.4 ml, or 1.5 ml.

[0043] In some embodiments, the material of the quantum dot light-emitting layer is a quantum dot with an organic ligand attached to the surface. Optionally, the organic ligand is at least one of the group consisting of oleic acid, oleylamine, octylamine, trioctylphosphine or trioctylphosphine oxide.

[0044] In some embodiments, the quantum dots are selected from at least one of the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, PbS, PbSe, PbTe, GaP, GaAs, InP, InAs, and binary, ternary, and quaternary II-VI compounds. Optionally, the quantum dots are CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, PbS, PbSe, PbTe, GaP, GaAs, InP, InAs, binary II-VI compounds, ternary II-VI compounds, quaternary II-VI compounds, InP / ZnSe / ZnS mixtures, CdSe / CdZnSe mixtures.

[0045] In some embodiments, the quantum dots are doped or undoped inorganic perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs, M is selected from at least one of the group consisting of Pb, Sn, Cu, Ni, Cd, Cr, Mn, Co, Fe, Ge, Yb and Eu, and X is selected from at least one of the group consisting of Cl, Br and I. Optionally, the quantum dots are CsPbCl3, CsPbClBr2, CsPbClI2, CsPbCl2Br, CsPbCl2I, CsPbClBrI, CsPbBr3, CsPbBr2I, CsPbBrI2, CsPbI3, CsSnCl3, CsSnBr3 or CsSnI3.

[0046] In some embodiments, the quantum dot is an organic-inorganic hybrid perovskite semiconductor; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is selected from CH3(CH2)n-2NH3 + or NH3(CH2)nNH3 2+ , and n≥2, M is selected from at least one of the group consisting of Pb, Sn, Cu, Ni, Cd, Cr, Mn, Co, Fe, Ge, Yb and Eu, and X is selected from at least one of the group consisting of Cl, Br and I. Optionally, the quantum dot is CH3CH2-2NH3PbCl3, CH3CH2-2NH3PbClBr2, CH3CH2-2NH3PbClI2, CH3CH2-2NH3PbCl2Br, CH3CH2-2NH3PbCl2I, CH3CH2-2NH3PbClBrI, CH3CH2-2NH3PbBr3, CH3CH2-2NH3PbBr2I, CH3CH2-2NH3PbBrI2, CH3CH2-2NH3PbI3, CH3(CH2)2-2 NH3PbCl3, CH3(CH2)2-2NH3PbClBr2, CH3(CH2)2-2NH3PbClI2, CH3(CH2)2-2NH3PbCl2Br, CH3(CH2)2-2NH3PbCl2I, CH3(CH2)2-2NH3PbClBrI, CH3(CH2)2-2NH3PbBr3, CH3(CH2)2-2NH3PbBr2I, CH3(CH2)2-2NH3PbBrI2 or CH3(CH2)2-2NH3PbI3.

[0047] (3) An electron transport layer and a metal cathode are sequentially formed on the processed quantum dot light-emitting layer.

[0048] In some embodiments, the material of the electron transport layer is selected from at least one of the group consisting of ZnO, TiO2, SnO2 and Alq3. Optionally, the material of the electron transport layer is ZnO, TiO2, SnO2, Alq3, a mixture of ZnO and TiO2, a mixture of ZnO and SnO2, a mixture of ZnO and Alq3, a mixture of TiO2 and SnO2, a mixture of TiO2 and Alq3, or a mixture of SnO2 and Alq3.

[0049] The present application provides an electroluminescent device, comprising an ITO substrate, a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer and a metal cathode stacked in sequence from bottom to top. The electroluminescent device is prepared by the above-mentioned preparation method of the electroluminescent device, and the electroluminescent device prepared by this method can enhance the effective recombination of electrons and holes and the exciton lifetime, so that the device performance is effectively improved.

[0050] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0051] Example 1

[0052] This embodiment provides an electroluminescent device, and the preparation process thereof is as follows:

[0053] First, 1.2mmol of indium acetate (In(Ac)3), 0.6mmol of zinc acetate (Zn(Ac)2) and 3.6mmol of palmitic acid (PA) were mixed and heated at 150°C for 30min to obtain a mixed solution, and then 0.8mmol of trimethylsilylphosphine (TMS)3P) was dissolved in 1ml of trioctylphosphine (TOP) and added to the above mixed solution, and then reacted at 290°C for 5min to obtain InP core; then the cleaned InP core was added to 5M (Note: M is mol / L) Zn(OA)2 solution, 0.2M Se-TOP solution was added at 110°C and the temperature was rapidly raised to 320°C, and 1M S-TOP solution was added. After reacting for 30min, the mixture was cleaned and dried, and OCT (a mixture of polyethylene glycol and polyvinyl alcohol) solution was added to obtain InP / ZnSe / ZnS solution.

[0054] The ITO substrate was cleaned with glass cleaner, deionized water, ethanol, acetone, and isopropanol in sequence, and then treated with UV ozone for 5 minutes. The PEDOT:PSS solution was spin-coated on the cleaned ITO substrate at a speed of 3000 rpm / min for 30 seconds, and then annealed at 140°C for 30 minutes to form a PEDOT:PSS film.

[0055] Then, the TFB solution was spin-coated on the PEDOT:PSS film at a speed of 2000 rpm / min for 30 seconds, and then annealed at 120°C for 20 minutes to form a TFB film. Subsequently, the InP / ZnSe / ZnS quantum dot solution was spin-coated on the TFB film at a speed of 4000 rpm / min for 45 seconds to form a quantum dot film.

[0056] Then, a proton solvent: ethanol solution (mass concentration of 50%) was spin-coated on the quantum dot film at a speed of 10000 rpm / min for 30 seconds. Through TEM test, it was found that the quantum dot film crystals treated with the proton solvent would show uniform diffraction rings and have uniform crystal orientation; then, it was annealed at 80°C for 15 minutes, and then a ZnO solution was spin-coated on the treated quantum dot film at speeds of 4000 rpm / min and 1500 rpm / min, respectively, for 30 seconds, and then annealed at 80°C for 30 minutes to obtain a ZnO film; finally, a metal Al electrode was deposited on the ZnO film to prepare an electroluminescent device.

[0057] Example 2

[0058] This embodiment provides an electroluminescent device, and the preparation process thereof is as follows:

[0059] First, 8mmol of cadmium oxide, 8ml of OA (oleic acid), and 72mL of ODE (octadecene) were mixed and heated to 240°C under vacuum conditions to completely convert them into cadmium oleate, and the temperature was continued to rise to 320°C. Then, TOP-Se precursor was quickly added thereto at 280°C, and the CdSe core was prepared after reaction for 5 minutes. The cleaned CdSe core was then added to 5M Zn(OA)2 solution, and at 315°C, 0.5M Se-TOP solution and 0.02M Cd-TOP solution were added at the same time. After reaction for 30 minutes, the solution was cleaned and dried, and OCT solution was added to obtain CdSe / CdZnSe solution.

[0060] The ITO substrate was cleaned with glass cleaner, deionized water, ethanol, acetone, and isopropanol in sequence, and then treated with UV ozone for 5 minutes. The PEDOT:PSS solution was spin-coated on the cleaned ITO substrate at a speed of 3000 rpm / min for 30 seconds, and then annealed at 140°C for 30 minutes to form a PEDOT:PSS film.

[0061] Then, the TFB solution was spin-coated on the PEDOT:PSS film at a rotation speed of 2000 rpm / min for 30 seconds, and then annealed at 120°C for 20 minutes to form a TFB film. Subsequently, the CdSe / CdZnSe quantum dot solution was spin-coated on the TFB film at a rotation speed of 4000 rpm / min for 45 seconds to form a quantum dot film.

[0062] Then, a proton solvent: ethanol solution is spin-coated on the quantum dot film at a rotation speed of 10000 rpm / min for 30 seconds, followed by annealing at 80°C for 15 minutes, and then a ZnO solution is spin-coated on the treated quantum dot film at rotation speeds of 4000 rpm / min and 1500 rpm / min for 30 seconds, respectively, and then annealed at 80°C for 30 minutes to obtain a ZnO film; finally, a metal Al electrode is deposited on the ZnO film to prepare an electroluminescent device.

[0063] Example 3

[0064] This embodiment provides an electroluminescent device, and its preparation process is different from that of Embodiment 1 in that the proton solvent: methanol solution is continuously spin-coated on the quantum dot film at a rotation speed of 10000 rpm / min, and the rest of the preparation process is the same.

[0065] Example 4

[0066] This embodiment provides an electroluminescent device, and its preparation process is different from that of Embodiment 1 in that a proton solvent: a mixed solution of methanol and ethanol is continuously spin-coated on the quantum dot film at a rotation speed of 10000 rpm / min, and the rest of the preparation process is the same.

[0067] Example 5

[0068] This embodiment provides an electroluminescent device, and its preparation process is different from that of Example 1 in that a proton solvent is further spin-coated at a speed of 10000 rpm / min on the quantum dot film formed by the prepared CsPbCl3 quantum dot solution, and the rest of the preparation process is the same.

[0069] Example 6

[0070] This embodiment provides an electroluminescent device, and its preparation process is different from that of Example 1 in that a proton solvent is further spin-coated at a speed of 10000 rpm / min on the quantum dot film formed by the prepared CH3CH2-2NH3PbCl3 quantum dot solution, and the rest of the preparation process is the same.

[0071] Comparative Example 1

[0072] This comparative example provides an electroluminescent device, and its preparation process is different from that of Example 1 in that the proton solvent is not spin-coated on the quantum dot film, and the rest of the preparation process is the same.

[0073] Comparative Example 2

[0074] This comparative example provides an electroluminescent device, and its preparation process is different from that of Example 2 in that the proton solvent is not spin-coated on the quantum dot film, and the rest of the preparation process is the same.

[0075] Comparative Example 3

[0076] This comparative example provides an electroluminescent device, and its preparation process is different from that of Example 1 in that the proton solvent is continuously spin-coated on the quantum dot film at a rotation speed of 4000 rpm / min, and the rest of the preparation process is the same.

[0077] Experimental example

[0078] 1. The devices prepared in the above-mentioned Examples 1-2 and Comparative Examples 1-2 were placed at 100°C for 10 hours to heat and remove the non-volatile reagents contained in the device structure, such as water, ethanol, etc., and then the film quality of the quantum dot light-emitting layer in the device was tested using the same testing instrument: Guangzhou Mingmei Optoelectronics Fluorescence Microscope. The results are shown in Figure 1. Figures 1 to 4 shown.

[0079] 2. Device performance: The devices prepared in the above Examples 1-6 and Comparative Examples 1-4 were placed at 100°C for 10 hours, and then the life and efficiency of the devices were tested using the same testing instrument: Ocean Optics EQE testing system. The results are shown in Table 1.

[0080] Table 1 Device performance test results

[0081]

[0082] contrast Figure 1 The corresponding film formation diagram of the quantum dot light-emitting layer in Example 1 is Figure 2 The corresponding film formation diagram of the quantum dot light-emitting layer in Comparative Example 1, and the comparison Figure 3 The corresponding film formation diagram of the quantum dot light-emitting layer in Example 2 is Figure 4 From the corresponding film formation diagram of the quantum dot light-emitting layer in Comparative Example 2, it can be seen that the film formation quality of the quantum dot light-emitting layer after spin coating with a proton solvent ethanol solution is significantly better than the film formation quality of the quantum dot light-emitting layer after spin coating without a proton solvent ethanol solution, indicating that spin coating the quantum dot light-emitting layer with a proton solvent ethanol solution can effectively improve the quality of the quantum dot film and eliminate surface defects (manifested as black spots and holes), thereby improving device performance.

[0083] Comparing the performance of the device prepared in Example 1 with the performance of the corresponding device prepared in Comparative Example 1, the performance of the device prepared after spin coating the quantum dot light-emitting layer with the proton solvent ethanol is significantly better than the performance of the device prepared without spin coating the quantum dot light-emitting layer with the proton solvent ethanol, indicating that spin coating the quantum dot light-emitting layer with the proton solvent ethanol can significantly improve the device performance.

[0084] The above description is only an embodiment of the present application and is not intended to limit the protection scope of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for processing a quantum dot light-emitting layer, characterized in that: The following steps are involved: Spin coating a proton solvent on the quantum dot light-emitting layer at a speed of 8000-10000 rpm / min for 0.5-1.5 min, and then heat treating the layer until the proton solvent evaporates; Wherein, the proton solvent comprises at least one of a composition consisting of methanol, ethanol, tert-butyl alcohol, and benzyl alcohol; the amount of the proton solvent spin-coated on the quantum dot light-emitting layer per unit centimeter area is 0.5-2 ml; The material of the quantum dot light-emitting layer is a quantum dot with an organic ligand connected to the surface; the quantum dot is selected from at least one of the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, PbS, PbSe, PbTe, GaP, GaAs, InP, InAs and ternary and quaternary II-VI compounds; and / or, the quantum dot is a perovskite semiconductor; the general structural formula of the perovskite semiconductor is AMX3 or BMX3, wherein A is Cs and B is selected from CH3(CH2)n-2NH3 + or NH3(CH2)nNH3 2+ , and n≥2, M is selected from at least one of the group consisting of Pb, Sn, Cu, Ni, Cd, Cr, Mn, Co, Fe, Ge, Yb and Eu, and X is selected from at least one of the group consisting of Cl, Br and I.

2. The method for processing a quantum dot light-emitting layer according to claim 1, characterized in that: The temperature of the heat treatment is 80-150° C., and the time of the heat treatment is 10-30 minutes.

3. An electroluminescent device, characterized in that: include: The following are stacked in order from bottom to top: an ITO substrate, a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer and a metal cathode, wherein the surface of the quantum dot light-emitting layer close to the electron transport layer is treated by the method for treating the quantum dot light-emitting layer as claimed in claim 1.

4. The electroluminescent device according to claim 3, characterized in that The material of the hole injection layer is selected from the group consisting of PEDOT:PSS, PTPDES, PTPDES:TPBAH, PFO-co-NEPBN, PFO-co-NEPBN:F4-TCNQ, MoO x , WO x , NiO and CuO.

5. The electroluminescent device according to claim 3, characterized in that: The material of the hole transport layer is at least one selected from the group consisting of TFB, PVK, TCTA, TPD, Poly:TPD and CBP.

6. The electroluminescent device according to claim 3, characterized in that: The material of the electron transport layer is at least one selected from the group consisting of ZnO, TiO2, SnO2 and Alq3.

7. A method for preparing an electroluminescent device, characterized in that: The following steps are involved: A hole injection layer and a hole transport layer are sequentially formed on an ITO substrate; A quantum dot light-emitting layer is formed on the hole transport layer, and a proton solvent is spin-coated on the quantum dot light-emitting layer at a speed of 8000-10000 rpm / min for 0.5-1.5 min, and then a heat treatment is performed to volatilize the proton solvent, the heat treatment temperature is 80-150° C., and the heat treatment time is 10-30 min; wherein the proton solvent includes at least one of a combination consisting of methanol, ethanol, tert-butyl alcohol, and benzyl alcohol; Sequentially forming an electron transport layer and a metal cathode on the processed quantum dot light-emitting layer; The amount of the proton solvent spin-coated on the quantum dot light-emitting layer per unit centimeter area is 0.5-2 ml; The material of the quantum dot light-emitting layer is a quantum dot with an organic ligand connected to the surface; the quantum dot is selected from at least one of the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, PbS, PbSe, PbTe, GaP, GaAs, InP, InAs and ternary and quaternary II-VI compounds; and / or, the quantum dot is a perovskite semiconductor; the general structural formula of the perovskite semiconductor is AMX3 or BMX3, wherein A is Cs and B is selected from CH3(CH2)n-2NH3 + or NH3(CH2)nNH3 2+ , and n≥2, M is selected from at least one of the group consisting of Pb, Sn, Cu, Ni, Cd, Cr, Mn, Co, Fe, Ge, Yb and Eu, and X is selected from at least one of the group consisting of Cl, Br and I.